"The lesser of two evils": a framework analysis of consumers' perspectives on opioid deprescribing and the development of opioid deprescribing guidelines. Issue 11 (24th November 2021) - Langford, Aili V.; Gnjidic, Danijela; Lin, Chung-Wei Christine; Bero, Lisa; Blyth, Fiona; Penm, Jonathan; Schneider, Carl R.
Abstract : Supplemental Digital Content is Available in the Text. Qualitative analysis of opioid consumers' perspectives may assist health practitioners and guideline developers in creating recommendations and interventions to facilitate opioid deprescribing through targeting behavioral change. Abstract: Deprescribing opioids has been identified as an intervention to mitigate opioid harm; however, it is often challenging to implement interventions and communicate deprescribing decisions to consumers. The development of opioid deprescribing guidelines may provide guidance and support on when and how to reduce or cease opioids in routine care. This study aimed to explore the perspectives of opioid consumers on opioid deprescribing and determine factors to be considered in the development of opioid deprescribing guidelines. A purposive sample of 20 consumers using opioids for pain was recruited. Semistructured interviews were conducted, audio recorded, and transcribed verbatim. Inductive thematic analysis was undertaken, followed by a framework analysis informed by Bandura's Social Cognitive Theory. Behavioral, cognitive, and environmental factors influence consumers' attitudes and actions regarding opioid deprescribing. Significant barriers to opioid deprescribing were identified, including fears of pain and withdrawal effects, opioid-related stigma, and perceived inadequacies of the healthcare system. Improved communication between healthcare professionals and consumers regarding expectations of deprescribing and goals of care, as well as the provision of greater opportunities for consumer engagement in decision making were identified as avenues to improve the success of opioid deprescribing. For opioid deprescribing guidelines to be effective and achieve the intended goal of optimizing opioid use, consumers need to feel empowered to engage in opioid reduction or cessation. The findings of this study may facilitate a patient-centred approach for practitioners and guideline developers in creating recommendations and interventions to enable opioid deprescribing through targeting behavioral change.